Thinking the Automobile. A Design and Engineering intention? - Santos,Ricardo Paulo da Silva Cameira dos (2022)
Abstract The relationship between Design and Engineering has not its genesis in the 20th century. But it was in this century that the advantage of this association was perceived and came into existence. From the beginning of mass production in the early twentieth century came the need for bringing the two disciplines together: Design and Engineering. Although Design and Engineering are two separate and independent disciplines, much of their applied field overlaps. The automotive product design and industry is a common ground where Design and Engineering strive to achieve, together, a common final product: the automobile. This article aims to discuss how the development of the automobile throughout the 20th and 21st centuries was driven by Design and Engineering, opening the way for a deeper debate on the definition of this interaction. A definition for the Product Development methodology from the Engineering and Design point of view is described, as well as the role of the Design and Engineering disciplines within the automotive product development. Methodologically, a historically relevant case study in the development of the automobile product is presented.